What is the difference between the blood–nerve barrier and blood–brain barrier?. Issue 1 (February 2017) - Nakatsuji, Yuji
Abstract: The blood–brain barrier and blood–nerve barrier play crucial roles in maintaining homeostasis of the central and peripheral nervous systems. Takeshita et al. reported the different molecular expression pattern in the components constituting the blood–brain barrier and blood–nerve barrier, and suggested that the blood–nerve barrier might have a distinct mechanism for T cell migration. Abstract : The BBB and BNB play crucial roles in maintaining homeostasis of central and peripheral nervous systems. Takeshita et al. reported the different molecular expression pattern in the components constituting BBB and BNB, and suggested that BNB might have distinct mechanism for T cell migration.